2021
DOI: 10.3389/fpls.2021.656657
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Small RNAs During High Light Acclimation in Arabidopsis thaliana

Abstract: The biological significance of non-coding RNAs (ncRNAs) has been firmly established to be important for the regulation of genes involved in stress acclimation. Light plays an important role for the growth of plants providing the energy for photosynthesis; however, excessive light conditions can also cause substantial defects. Small RNAs (sRNAs) are a class of non-coding RNAs that regulate transcript levels of protein-coding genes and mediate epigenetic silencing. Next generation sequencing facilitates the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 125 publications
(176 reference statements)
0
15
0
Order By: Relevance
“…1 d). The involvement of miR163 and miR840 in the HL response is not surprising because miR163 was previously found to be induced by light during seedling de-etiolation [ 47 , 48 ] after 6 h of HL [ 12 ] or red light treatment [ 49 ], and miR840 was described as a gamma-ray-responsive miRNA [ 16 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 d). The involvement of miR163 and miR840 in the HL response is not surprising because miR163 was previously found to be induced by light during seedling de-etiolation [ 47 , 48 ] after 6 h of HL [ 12 ] or red light treatment [ 49 ], and miR840 was described as a gamma-ray-responsive miRNA [ 16 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, far-red light-responsive miRNAs were described in soybean [ 10 ]. Nevertheless, there is almost no information about miRNA expression changes under high light (HL) conditions except studies on Dendrocalamus latiflorus , an important Asian bamboo species [ 11 ], a recent report describing small RNAs during high light acclimation [ 12 ] and the systemic miRNA response in Arabidopsis thaliana roots [ 13 ]. Additionally, there are some reports on UV-A-, UV-B-, and gamma radiation-regulated miRNAs [ 14 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oryza sativa subjected to continuous dark treatment showed a decrease in the catalase gene ( Cat B ) expression in roots caused by an accumulation of Cat B sense and antisense unspliced transcripts, detected by RNA dot-plot hybridization [ 36 ]. In contrast, Tiwari et al [ 100 ] used strand-specific RNAseq to investigate small RNA induced by high light acclimation in A. thaliana and detected NATs and double-strand RNAs derived from NATs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports also revealed that sRNAs are crucial for abiotic stress tolerance mechanisms in various plant species (Fu et al, 2017, Tiwari et al, 2021 and due to the anticipated adjustment and/or misregulation of sRNA biogenesis and sRNA-directed gene regulatory networks, we hypothesized that plants with mutated MpDCLs would have altered abiotic stress tolerance. High salinity is one of the most severe abiotic stresses that induces global transcriptomic changes and adversely affects plant growth and development (Golldack et al, 2011, Fu et al, 2017, Tanaka et al, 2018.…”
Section: Effects Of Mpdcl Mutations On Thallus Developmentmentioning
confidence: 99%